Does the Change in Land Cover Alters Birds and Butterflies Diversity? - Marini Machdi Putri; Yanto Santosa; Burhanuddin Masy'ud (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2021)
Currently the expansion of oil palm is increasing, which at the same time creates a lot of negative responses related to environmental impacts, biodiversity loss, including birds and butterflies species diversity. Nowadays our understanding of the impacts of oil palm plantations is still based on the claim that oil palm plantations are established on primary forest land. The study aimed to estimate the impact of land cover changes, loss of biodiversity, and possible cohabitation between birds and butterflies based on baseline land type before oil palm plantation. The research was conducted at PT Tempirai Palm Resources, to be precise, in the baseline area (shrubs) and plantation areas planted with oil palm using direct and indirect observation methods. Based on research, it was known that land conversion to oil palm plantations caused changes in the number of species, and the diversity of birds and butterflies. The number of bird species in the baseline area was higher (S = 22 species, H ‘= 2.51) than in the plantation area. The number of butterfly species in the baseline area was less (0 species) than in the oil palm plantation area (5 species, H ‘= 1.56, Dmg = 2.23). In general, the increase in bird species’ biodiversity was higher (59.09%) compared to the loss. In contrast, the butterfly species was not lost. A cohabitation also occurred between birds and butterflies at the site. The study concluded that oil palm plantation not only have a negative impact but also a positive impact for biodiversity especially for bird and butterfly.